N-doped defective carbon loaded amorphous Co nanoparticle composite material and preparation method and application thereof

By using N-doped defective carbon-supported amorphous Co nanoparticle composite as a catalyst, the problem of secondary pollution and low activation efficiency of water caused by catalysts in the prior art is solved, and microcystoxin and sulfamethyla in water is realized. The efficient removal of azoles has good stability and regeneration ability.

CN119215897APending Publication Date: 2024-12-31HEQING COUNTY FORESTRY ECOLOGICAL INVESTMENT & DEVELOPMENT CO LTD +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411104272.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

When the existing catalysts activate monosulfate, metal ions are easily leaching, causing secondary contamination of the water body, and have low activation efficiency, making it difficult to efficiently remove microcystistoxin and sulfamethoxazole in the water body.

Method used

The N-doped defective carbon-supported amorphous Co nanoparticle composite material is used as a catalyst. By mixing water-soluble cobalt salt and coffee residue biochar, it is freeze-dried and calcined to form amorphous Co nanoparticles supported on the defective carbon skeleton. Improves the activation efficiency of PMS and reduces the amount of metal leaching.

Benefits of technology

It has achieved efficient removal of microcystis toxin and sulfamethoxazole in water, avoided secondary pollution of water, and the catalyst has good regeneration ability and stability, which is suitable for long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215897A_ABST
    Figure CN119215897A_ABST
Patent Text Reader

Abstract

The invention provides an N-doped defective carbon loaded amorphous Co nano-particle composite material as well as a preparation method and application thereof, and belongs to the field of preparation and treatment of environment functional materials. The invention provides an N-doped defective carbon loaded amorphous Co nano-particle composite material. The N-doped defective carbon loaded amorphous Co nano-particle composite material comprises an N-doped defective carbon skeleton and amorphous Co nano-particles loaded in the N-doped defective carbon skeleton. The N-doped defective carbon-loaded amorphous Co nanoparticle composite material provided by the invention is small in metal leaching amount, high in regeneration capacity and good in stability, has excellent removal capacity on microcystic toxins LR and SMX in water when being used as a catalyst for activating PMS, and can realize long-term utilization of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation and treatment of environmental functional materials, and specifically relates to an N-doped defective carbon-loaded amorphous Co nanoparticle composite material and a preparation method and application thereof. Background Art

[0002] The N and P content in water bodies continues to rise, causing eutrophication in many natural water bodies. At the same time, it is accompanied by the massive reproduction of algae and the occurrence of algal blooms. my country's Dianchi Lake, Taihu Lake and Chaohu Lake are deeply troubled by blue-green algae blooms.

[0003] In addition to polluting lake water, the outbreak of cyanobacteria blooms also releases a large amount of algal toxins into the water. The most common and most toxic cyanobacterial toxins in cyanobacteria blooms are called microcystins (MCs). MCs are usually a fixed sequence consisting of 5 amino acids (Adda, Glu, Mdha, Ala, MeAsp) and 2 variable amino acids (represented by X and Y). Different combinations of X and Y will form a variety of MCs isomers, such as MC-LR, MC-RR and MC-YR (L, R, Y represent leucine, arginine and tyrosine, respectively).

[0004] MC-LR is the most common form of MCs, accounting for 46-99.8% of the total concentration of MCs in cyanobacteria. At the same time, MC-LR also has the strongest acute toxin, followed by MC-YR, and MC-RR has the weakest toxicity. MC-LR is also classified as a Class 2B carcinogen by the International Agency for Research on Cancer. After MC-LR is ingested, it will quickly enter the liver through carrier proteins and inhibit the activity of protein phosphatases in liver cells. MC-LR also promotes the expression of carcinogens and induces cancer. In addition, there are exogenous pollutants in water bodies, such as sulfamethoxazole (SMX). Therefore, the development of a technology for efficiently removing pollutants from water bodies is of great significance to the restoration of polluted water bodies and the protection of the ecological environment.

[0005] Persulfate has high redox potential, wide pH operating range, long half-life and stability, and can effectively remove MC-LR and SMX. 2+ , Mn 2+ or Fe 2+ Various transition metal ions can generate ·O and SO4· - And other free radicals, thereby achieving efficient removal of MC-LR and SMX.

[0006] At present, the catalysts for activating PMS are generally Co-based catalysts and carbon-based catalysts. Co-based catalysts are prone to leaching metal ions during use, which is likely to exceed the Co concentration of less than 1.0 mg·L in the "Surface Water Environmental Quality Standard" (GB3838-2002).-1 The requirements of the catalyst will cause secondary pollution to the water body; the carbon-based catalyst has the problem of slow activation efficiency. Therefore, it is urgent to provide a catalyst with high activation efficiency and no secondary pollution to the water body. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide an N-doped defective carbon-supported amorphous Co nanoparticle composite material and its preparation method and application. The N-doped defective carbon-supported amorphous Co nanoparticle composite material provided by the present invention has a small amount of metal leaching, does not cause secondary pollution of water bodies, and has a high activation efficiency for PMS.

[0008] In order to achieve the above object, the present invention provides the following scheme:

[0009] The invention provides an N-doped defective carbon-loaded amorphous Co nanoparticle composite material, comprising an N-doped defective carbon skeleton and amorphous Co nanoparticles loaded in the N-doped defective carbon skeleton.

[0010] Preferably, the mass of the amorphous Co nanoparticles is 1-2% of the mass of the N-doped defective carbon-supported amorphous Co nanoparticle composite material.

[0011] Preferably, in the N-doped defective carbon skeleton, the doping amount of N atoms is 35-40%.

[0012] The present invention provides a method for preparing the N-doped defective carbon-supported amorphous Co nanoparticle composite material described in the above scheme, comprising the following steps:

[0013] The water-soluble cobalt salt, coffee grounds biochar and water are mixed, and after solid-liquid separation, the obtained solid matter is freeze-dried to obtain biochar loaded with Co ions;

[0014] The biochar loaded with Co ions and a nitrogen source are mixed and calcined to obtain the N-doped defective carbon loaded amorphous Co nanoparticle composite material; the nitrogen source is dicyandiamide or melamine.

[0015] Preferably, the water-soluble cobalt salt includes Co(NO3)2·6H2O; the mass of the water-soluble cobalt salt is 0 to 9.5% of the mass of the coffee grounds biochar, and is not 0.

[0016] Preferably, the freeze-drying temperature is 10 to 70° C. and the time is 12 to 24 hours.

[0017] Preferably, the mass ratio of the biochar loaded with Co ions to the nitrogen source is 1:(5-20).

[0018] Preferably, the calcination temperature is 600-800° C. and the holding time is 2 hours.

[0019] Preferably, the heating rate to the calcination temperature is 3-8°C / min.

[0020] The present invention provides the N-doped defective carbon-loaded amorphous Co nanoparticle composite material described in the above scheme or the N-doped defective carbon-loaded amorphous Co nanoparticle composite material prepared by the preparation method described in the above scheme, and uses them as catalysts in catalyzing peroxymonosulfate to degrade water pollutants.

[0021] The invention provides an N-doped defective carbon-loaded amorphous Co nanoparticle composite material, comprising an N-doped defective carbon skeleton and amorphous Co nanoparticles loaded in the N-doped defective carbon skeleton.

[0022] The N-doped defective carbon-loaded amorphous Co nanoparticle composite material provided by the present invention is a composite structure in which amorphous Co particles are loaded on a defective carbon skeleton, which provides multiple active sites for metal and carbon materials. Amorphous Co excites free radical processes, and defective carbon materials excite non-radical oxidation processes. The two processes occur simultaneously during the activation process, thereby improving the activation efficiency of PMS.

[0023] The N-doped defective carbon-supported amorphous Co nanoparticle composite material provided by the present invention exhibits low metal leaching (in the cycle diagram test of composite material degradation MC-LR, the leaching amounts from the first cycle to the fifth cycle are 0.853 mg·L -1 、0.587mg·L -1 , 0.439mg·L -1 , 0.354mg·L -1 and 0.273 mg·L -1 ), strong regeneration ability and good stability. When used as a catalyst to activate PMS, it has excellent removal ability for microcystin LR and SMX in water and can achieve long-term utilization of the catalyst.

[0024] The present invention adopts vacuum freeze drying and thermal oxidation process (calcination) to prepare N-doped defective carbon-loaded amorphous Co nanoparticle composite material, wherein the amorphous Co nanoparticles are uniformly loaded in the N-doped defective carbon skeleton, and the carbon skeleton material generates nitrogen-containing gas during thermal oxidation (calcination) of a N source (dicyandiamide or melamine), and a pore structure is formed during the process of bubbles penetrating from the inside to the outer surface of the material, thereby promoting the high dispersion of Co active substances and the electron transfer process.

[0025] The preparation method provided by the present invention is simple, and uses coffee grounds biochar as a raw material, thereby being able to realize the recycling of solid waste coffee grounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0027] Figure 1 The Co-NCG prepared in Example 2 15 The morphology and structure of the catalyst;

[0028] Figure 2 The Co-NCG prepared in Example 2 15 XRD pattern of catalyst (a); Co-NCG 15 Raman spectra of CG (b); Co-NCG 15 Adsorption-desorption curve and pore size distribution diagram (c); Co-NCG 15 XPS images (d) to (h);

[0029] Figure 3 For Co-NCG 15 +PMS added to sulfamethoxazole (SMX) solution UV spectrum change over time (a); Co-NCG prepared at different temperatures 15 Changes in SMX removal rate (b); Co-NCG prepared with different CoNO3·6H2O addition concentrations 15 Changes in SMX removal rate (c); Co-NCG prepared at different calcination temperatures 15 Effect of SMX removal on removal efficiency (d);

[0030] Figure 4 Co-NCG when different concentrations of PMS are added 15 + PMS system MC-LR removal rate (a); different concentrations of Co-NCG 15 Co-NCG 15 + PMS system MC-LR removal rate (b); Effect of initial dissolution pH on Co-NCG 15 +PMS system to remove MC-LR removal efficiency (c); Inorganic ions and humic acid on Co-NCG 15 + Effect of the removal efficiency of MC-LR by PMS system (d);

[0031] Figure 5 For Co-NCG 15 Quenching diagram of MC-LR degradation (a); DMPOX image (b), DMPO (DMPO-SO4 ·- , DMPO-·OH)(c) and DMPO(DMPO-O2·- )(d);TEMP(TEMP- 1 EPR spectrum of O2 as a scavenger (e) Co-NCG 15 (f) Cycle diagram of multiple degradation of MC-LR. DETAILED DESCRIPTION

[0032] The invention provides an N-doped defective carbon-loaded amorphous Co nanoparticle composite material, comprising an N-doped defective carbon skeleton and amorphous Co nanoparticles loaded in the N-doped defective carbon skeleton.

[0033] In the present invention, the mass of the amorphous Co nanoparticles is preferably 1-2% of the mass of the N-doped defective carbon-supported amorphous Co nanoparticle composite material, and more preferably 1.26%. In the N-doped defective carbon skeleton, the doping amount of N atoms is preferably 35-40%, and more preferably 39.35%.

[0034] In the present invention, the particle size of the amorphous Co nanoparticles is preferably 10 to 30 nm. In the present invention, the average pore size of the N-doped defective carbon-supported amorphous Co nanoparticle composite material is preferably 2 to 3 nm, specifically 2.091 nm in the embodiment.

[0035] The N-doped defective carbon-loaded amorphous Co nanoparticle composite material provided by the present invention is a composite structure in which amorphous Co particles are loaded on a defective carbon skeleton, which provides multiple active sites for metal and carbon materials. Amorphous Co excites free radical processes, and defective carbon materials excite non-radical oxidation processes. The two processes occur simultaneously during the activation process, thereby improving the activation efficiency of PMS.

[0036] The N-doped defective carbon-loaded amorphous Co nanoparticle composite material provided by the present invention has a small amount of metal leaching, strong regeneration ability, and good stability. When used as a catalyst for activating PMS, it has excellent removal ability for microcystin LR and SMX in water, and can achieve long-term utilization of the catalyst.

[0037] The present invention provides a method for preparing the N-doped defective carbon-supported amorphous Co nanoparticle composite material described in the above scheme, comprising the following steps:

[0038] The water-soluble cobalt salt, coffee grounds biochar and water are mixed, and after solid-liquid separation, the obtained solid matter is freeze-dried to obtain biochar loaded with Co ions;

[0039] The biochar loaded with Co ions and a nitrogen source are mixed and calcined to obtain the N-doped defective carbon loaded amorphous Co nanoparticle composite material; the nitrogen source is dicyandiamide or melamine.

[0040] Unless otherwise specified, the materials and equipment used in the present invention are commercially available.

[0041] The present invention mixes water-soluble cobalt salt, coffee grounds biochar and water, separates the solid and the liquid, and freeze-dries the obtained solid matter to obtain biochar loaded with Co ions.

[0042] In the present invention, the coffee grounds biochar is preferably obtained by removing ash from coffee grounds. Specifically, coffee grounds from a Ruixin coffee shop of Yunnan University are soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and dried at 60°C for 12 hours to obtain coffee grounds biochar for later use.

[0043] In the present invention, the water-soluble cobalt salt preferably includes Co(NO3)2·6H2O; the mass of the water-soluble cobalt salt is preferably 0 to 9.5% of the mass of the coffee grounds biochar, and is not 0, further preferably 2 to 8%, and more preferably 3 to 7.5%.

[0044] The present invention has no special requirement on the amount of water used, as long as it can dissolve Co(NO3)2·6H2O.

[0045] In the present invention, the mixing temperature is preferably 25° C., and the mixing time is preferably 6 hours; and the mixing is preferably performed under stirring conditions.

[0046] The present invention loads Co ions on the surface of the coffee grounds biochar through mixing.

[0047] The present invention has no special requirements for the solid-liquid separation, and a separation method well known in the art, such as filtration, can be used.

[0048] After the solid-liquid separation is completed, the present invention preferably washes the obtained solid matter. In the present invention, the washing is preferably carried out three times by alternating ethanol and deionized water with a pH value of 5 to 7. The present invention can remove other impurities that cannot be fixed on the surface of biochar by washing.

[0049] In the present invention, the freeze-drying temperature is preferably 10-70°C, more preferably 20-60°C, and more preferably 30-50°C; the freeze-drying time is preferably 12-24h, more preferably 13-22h, and more preferably 15-20h.

[0050] After obtaining the biochar loaded with Co ions, the present invention mixes the biochar loaded with Co ions with a nitrogen source and calcines them to obtain the N-doped defective carbon loaded amorphous Co nanoparticle composite material; the nitrogen source is dicyandiamide or melamine.

[0051] Before the calcination, the present invention also preferably grinds the mixture of the biochar loaded with Co ions and the nitrogen source.

[0052] In the present invention, the grinding time is preferably 2 hours. The present invention can fully mix the biochar loaded with Co ions and the nitrogen source through grinding, so that the biochar loaded with Co ions can fully react with the nitrogen source in the subsequent nitrogen doping process.

[0053] In the present invention, the mass ratio of the biochar loaded with Co ions to the nitrogen source is preferably 1:(5-20), more preferably 1:(10-20), and more preferably 1:15.

[0054] In the present invention, the calcination temperature is preferably 600-800°C, more preferably 650-750°C, and more preferably 680-730°C; the calcination holding time is preferably 2h. In the present invention, the calcination is preferably carried out in a nitrogen atmosphere.

[0055] In the present invention, the heating rate to the calcination temperature is preferably 3 to 8° C. / min, more preferably 5° C. / min.

[0056] In the calcination process of the present invention, as the calcination temperature changes, the coffee grounds biochar has carbon defects due to nitrogen doping, Co attached to the surface of the coffee grounds biochar is embedded in the carbon layer, and Co changes to an amorphous state; if a low temperature is used, the coffee grounds biochar has fewer defects and a low nitrogen doping amount, which leads to low degradation efficiency of the coffee grounds biochar as a catalyst for catalyzing PMS to degrade pollutants (microcystin LR and SMX) in water bodies.

[0057] The present invention adopts vacuum freeze drying and thermal oxidation process (calcination) to prepare N-doped defective carbon-loaded amorphous Co nanoparticle composite material, wherein the amorphous Co nanoparticles are uniformly distributed and loaded in the N-doped defective carbon skeleton, and the carbon skeleton material generates nitrogen-containing gas during thermal oxidation (calcination) of a N source (dicyandiamide or melamine), and a pore structure is formed during the process of gas bubbles penetrating from the inside to the outer surface of the material, thereby promoting the high dispersion of Co active substances and the electron transfer process.

[0058] The preparation method provided by the present invention is simple, and uses coffee grounds biochar as a raw material, thereby being able to realize the recycling of solid waste coffee grounds.

[0059] The present invention provides the N-doped defective carbon-loaded amorphous Co nanoparticle composite material described in the above scheme or the N-doped defective carbon-loaded amorphous Co nanoparticle composite material prepared by the preparation method described in the above scheme, and uses them as catalysts in catalyzing peroxymonosulfate to degrade water pollutants.

[0060] In the present invention, the application method is preferably: dispersing the N-doped defective carbon-loaded amorphous Co nanoparticle composite material in a water body containing pollutants, and then adding PMS for catalytic degradation.

[0061] In the present invention, the application temperature is preferably 25°C, and the concentration of the N-doped defective carbon-supported amorphous Co nanoparticle composite material is preferably 0.1 to 0.20 g·L -1 When used in the above-mentioned manner, the pH value of the water containing pollutants is preferably 3.00 to 9.00, the concentration of PMS is preferably 0.13 to 0.32 mM, and the concentration of pollutants is preferably 2.5 to 10 mg·L -1 .

[0062] To further illustrate the present invention, an N-doped defective carbon-loaded amorphous Co nanoparticle composite material provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0063] Example 1

[0064] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0065] 0.714 g of cobalt nitrate hexahydrate and 10 g of coffee grounds biochar were added to 150 mL of water and stirred for 6 h at room temperature. After filtering, the mixture was washed alternately with ethanol and deionized water with a pH value of 5 to 7 for 3 times. The solid was freeze-dried overnight to obtain biochar loaded with Co ions.

[0066] The biochar loaded with Co ions and dicyandiamide were fully mixed and ground at a mass ratio of 1:10 for 2 hours, and then placed in a tube furnace, heated from 25°C to 800°C at a heating rate of 5°C / min, and kept warm for 2 hours to obtain the N-doped defective carbon-loaded amorphous Co nanoparticle composite material, recorded as Co-NCG 10 catalyst.

[0067] Example 2

[0068] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0069] 0.714 g of cobalt nitrate hexahydrate and 10 g of coffee grounds biochar were added to 150 mL of water and stirred for 6 h at room temperature. After filtering, the mixture was washed alternately with ethanol and deionized water with a pH value of 5 to 7 for 3 times. The solid was freeze-dried overnight to obtain biochar loaded with Co ions.

[0070] The biochar loaded with Co ions and dicyandiamide were fully mixed and ground at a mass ratio of 1:15 for 2 hours, and then placed in a tube furnace, heated from 25°C to 800°C at a heating rate of 5°C / min, and kept warm for 2 hours to obtain the N-doped defective carbon-loaded amorphous Co nanoparticle composite material, recorded as Co-NCG 15 (also known as Co-NCG in performance testing 15 -800 or 3M) catalyst.

[0071] Example 3

[0072] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0073] 0.714 g of cobalt nitrate hexahydrate and 10 g of coffee grounds biochar were added to 150 mL of water and stirred for 6 h at room temperature. After filtering, the mixture was washed alternately with ethanol and deionized water with a pH value of 5 to 7 for 3 times. The solid was freeze-dried overnight to obtain biochar loaded with Co ions.

[0074] The biochar loaded with Co ions and dicyandiamide were fully mixed and ground in a mass ratio of 1:20, and then placed in a tube furnace, heated from 25°C to 800°C at a heating rate of 5°C / min, and kept warm for 2h to obtain the N-doped defective carbon-loaded amorphous Co nanoparticle composite material, recorded as Co-NCG 20 catalyst.

[0075] Example 4

[0076] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0077] 0.714 g of cobalt nitrate hexahydrate and 10 g of coffee grounds biochar were added to 150 mL of water and stirred for 6 h at room temperature. After filtering, the mixture was washed alternately with ethanol and deionized water with a pH value of 5 to 7 for 3 times. The solid was freeze-dried overnight to obtain biochar loaded with Co ions.

[0078] The Co ion-loaded biochar and melamine were fully mixed and ground in a mass ratio of 1:20, and then placed in a tube furnace, heated from 25°C to 800°C at a heating rate of 5°C / min, and kept warm for 2h to obtain the N-doped defective carbon-loaded amorphous Co nanoparticle composite material, recorded as Co-NDG 20 catalyst.

[0079] Example 5

[0080] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0081] 0.714 g of cobalt nitrate hexahydrate and 10 g of coffee grounds biochar were added to 150 mL of water and stirred for 6 h at room temperature. After filtering, the mixture was washed alternately with ethanol and deionized water with a pH value of 5 to 7 for 3 times. The solid was freeze-dried overnight to obtain biochar loaded with Co ions.

[0082] The treated biochar and dicyandiamide were fully mixed and ground in a mass ratio of 1:15, and then placed in a tube furnace, heated from 25°C to 600°C at a heating rate of 5°C / min, and kept warm for 2h to obtain the N-doped defective carbon-supported amorphous Co nanoparticle composite material, recorded as Co-NCG 15 -600 catalyst.

[0083] Example 6

[0084] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0085] 0.714 g of cobalt nitrate hexahydrate and 10 g of coffee grounds biochar were added to 150 mL of water and stirred for 6 h at room temperature. After filtering, the mixture was washed alternately with ethanol and deionized water with a pH value of 5 to 7 for 3 times. The solid was freeze-dried overnight to obtain biochar loaded with Co ions.

[0086] The treated biochar and dicyandiamide were fully mixed and ground in a mass ratio of 1:15, and then placed in a tube furnace, heated from 25°C to 700°C at a heating rate of 5°C / min, and kept warm for 2h to obtain the N-doped defective carbon-supported amorphous Co nanoparticle composite material, recorded as Co-NCG 15 -700 catalyst.

[0087] Example 7

[0088] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0089] 0.714 g of cobalt nitrate hexahydrate and 10 g of coffee grounds biochar were added to 150 mL of water and stirred for 6 h at room temperature. After filtering, the mixture was washed alternately with ethanol and deionized water with a pH value of 5 to 7 for 3 times. The solid was freeze-dried overnight to obtain biochar loaded with Co ions.

[0090] The biochar loaded with Co ions and dicyandiamide were fully mixed and ground in a mass ratio of 1:5, and then placed in a tubular furnace, heated from 25°C to 800°C at a heating rate of 5°C / min, and kept warm for 2 hours to obtain the N-doped defective carbon-loaded amorphous Co nanoparticle composite material, recorded as Co-NCG5 catalyst.

[0091] Example 8

[0092] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0093] 0.481 g of cobalt nitrate hexahydrate and 10 g of coffee grounds biochar were added to 150 mL of water and stirred for 6 h at room temperature. After filtering, the mixture was washed alternately with ethanol and deionized water with a pH value of 5 to 7 for 3 times. The solid was freeze-dried overnight to obtain biochar loaded with Co ions.

[0094] The treated biochar and dicyandiamide were fully mixed and ground in a mass ratio of 1:15, and then placed in a tubular furnace and heated from 25°C to 800°C at a heating rate of 5°C / min and kept warm for 2h to obtain the N-doped defective carbon-loaded amorphous Co nanoparticle composite material, recorded as 2M catalyst.

[0095] Comparative Example 1

[0096] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0097] The treated biochar was placed in a tubular furnace, heated from 25°C to 800°C at a heating rate of 5°C / min, and kept warm for 2 hours to obtain the defective carbon-loaded amorphous Co nanoparticle composite material, which was recorded as CG catalyst.

[0098] Comparative Example 2

[0099] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0100] The treated biochar and dicyandiamide were fully mixed and ground in a mass ratio of 1:15, and then placed in a tube furnace, heated from 25°C to 800°C at a heating rate of 5°C / min, and kept warm for 2h to obtain the N-doped defective carbon-supported amorphous Co nanoparticle composite material, denoted as NCG. 15 (also known as 0M) catalyst in performance testing.

[0101] Comparative Example 3

[0102] Coffee grounds from a Ruixin coffee shop in Yunnan University were soaked in 1 mol / L dilute hydrochloric acid at 25°C to remove ash, and then dried at 60°C for 12 hours to obtain coffee grounds biochar for later use;

[0103] 0.964 g of cobalt nitrate hexahydrate and 10 g of coffee grounds biochar were added to 150 mL of water and stirred for 6 h at room temperature. After filtering, the mixture was washed alternately with ethanol and deionized water with a pH value of 5 to 7 for 3 times. The solid was freeze-dried overnight to obtain biochar loaded with Co ions.

[0104] The treated biochar and dicyandiamide were fully mixed and ground in a mass ratio of 1:15, and then placed in a tubular furnace, heated from 25°C to 800°C at a heating rate of 5°C / min, and kept warm for 2 hours to obtain the N-doped defective carbon-loaded amorphous Co nanoparticle composite material, recorded as 4M catalyst.

[0105] Structure and performance testing

[0106] Figure 1 The Co-NCG prepared in Example 2 15 The morphology and structure of the catalyst, where (a) is CG and (b) to (c) are Co-NCG. 15 (d) to (e) are field emission scanning electron microscopy (FE-SEM) images; (f) to (j) are high magnification transmission electron microscopy (HRTEM) images; and (f) to (j) are TEM-EDS spectra.

[0107] Figure 1 (a) to (c) show that compared with the smooth native coffee carbon (a), the Co-NCG obtained in (b) 15It exhibits an obvious porous flocculent structure, which may be due to the evaporation of a large amount of dicyandiamide precursor during the pyrolysis process, leading to the formation of topological defects. At the same time, some metal particles can be observed in the flocs in (c). Through the TEM image of (d), it can be observed that the Co particles of 10 to 30 nm are evenly dispersed, which is consistent with the SEM results in (c), which is conducive to the activation of PMS by Co nanoparticles and the improvement of degradation performance. No obvious lattice fringes of Co and its oxides were found in the TEM image of (e), but it was observed that the nanoparticles were uniformly loaded on the carbon layer, which is conducive to reducing the shedding of nanoparticles during the reaction. In addition Figure 1 TEM-EDS spectra of (f) to (j) further confirm that Co-NCG 15 It contains C, N, O, and Co elements, and the amorphous Co particles are distributed in a relatively uniform state.

[0108] Figure 2 The Co-NCG prepared in Example 2 15 XRD pattern of catalyst (a); Co-NCG 15 Raman spectra of CG (b); Co-NCG 15 Adsorption-desorption curve and pore size distribution diagram (c); Co-NCG 15 XPS images (d) to (h).

[0109] Figure 2 (a) shows CG and NCG 15 and Co-NCG 15 In the XRD image, the diffraction peaks of graphite carbon are observed at about 26° and 44°, corresponding to the (002) and (100) planes on the graphite carbon JCPDS25-0284 card, respectively. At the same time, when N is doped into CG, the diffraction peak of graphitized carbon becomes broadened, which may be due to the increase in the N content in the carbon skeleton. After adding Co to the carbon skeleton, the same phenomenon of diffraction peak broadening is also observed. Co-NCG 15 No diffraction peaks of cobalt and cobalt oxide were observed in the diffraction peaks, which indicates that the cobalt in the catalyst is amorphous.

[0110] Depend on Figure 2 (b) Raman spectra show that CG and Co-NCG 15 Two typical D and G bands appeared, located at 1350 and 1580 cm respectively. -1 The extent of carbon defects and disordered structure can be measured by the intensity ratio of these two peaks (I D / I G ) to evaluate. From the results shown in (b), we can see that the I D / I G The value is 1.86, while Co-NCG 15Increased to 3.12. Prepared Co-NCG 15 The catalyst produced more defect structures than the original CG.

[0111] N2 adsorption-desorption isotherms investigated the 15 The specific surface area and average pore size. Figure 2 As shown in (c), Co-NCG 15 It presents a typical IV-type isotherm with a specific surface area of ​​249.725 m 2 / g, and its average pore size is 2.09056nm. The pore size distribution curve in the illustration in the upper left corner of (c) also proves that the catalyst has rich mesopore characteristics after one-step pyrolysis.

[0112] like Figure 2 The XPS high-resolution spectrum shown in (d) proves that the prepared catalytic material mainly includes four elements: Co 2p, N 1s, O1s, and C 1s.

[0113] in Figure 2 In (e), the peaks at 398.46 eV, 399.64 eV, 400.93 eV, and 402.78 eV correspond to pyrrolic nitrogen, pyridinic nitrogen, graphitic nitrogen, and oxidized nitrogen in N1s, respectively. Figure 2 (f) shows the spectrum of Co2p. The Co2p spectrum mainly includes 6 main peaks, among which the spectra at binding energies of 778.02eV and 793.96eV correspond to Co 2p3 / 2 and Co 2p1 / 2 of Co(Ⅲ). The binding energies of 781.98eV and 797.74eV are mainly Co(Ⅱ), while 785.39eV and 801.08eV correspond to Co 2p3 / 2 and Co2p1 / 2 satellite peaks. The peaks at 777.39eV and 791.68eV are attributed to metal Co.

[0114] Figure 2 As shown in the (g)O 1s spectrum, the binding energy peaks are mainly located at 530.88 eV, 531.96 eV and 533.36 eV, corresponding to OC=O, C=O and COC, respectively. Figure 2 The peaks at binding energies of 284.06 eV, 285.08 eV, 287.68 eV and 290.93 eV in the C1s spectrum in (h) correspond to CC / C=C, CO, OC=O and π excitations, respectively.

[0115] Figure 3 For Co-NCG 15 +PMS added to SMX solution UV spectrum change over time (a); Co-NCG prepared at different temperatures 15Changes in SMX removal rate (b); Co-NCG prepared with different CoNO3·6H2O addition concentrations 15 Changes in SMX removal rate (c); Co-NCG prepared at different calcination temperatures 15 Effect of removal of MC-LR on removal efficiency (d).

[0116] Figure 3 (a) shows the Co-NCG under different reaction times 15 Changes in the UV-visible spectrum of sulfamethoxazole (SMX) degraded by the / PMS reaction system. The specific test steps are as follows:

[0117] In the SMX degradation experiment, in order to determine the catalytic activity of the catalyst for SMX degradation, Co-NCG 15 Composite material (Co-NCG 15 The concentration of the composite material in the SMX aqueous solution was 0.2 g·L -1 ) dispersed in 50mL, 10mg·L -1 , pH = 5.50 SMX aqueous solution in a 100mL conical flask, oscillate in a constant temperature oscillator at 150rpm, 25°C for 1 minute, then add PMS to the solution (the concentration of PMS in the SMX aqueous solution is 0.32mM), start the catalytic degradation reaction, after a certain reaction time (3 minutes, 5 minutes, 10 minutes, 15 minutes and 20 minutes), take out the sample with a 2mL syringe, filter it with a 0.45 micron needle organic filter, and then measure the concentration change of the SMX sample at a wavelength of 265 nanometers by ultraviolet visible spectrophotometry. Its standard curve is y = 0.042x + 0.001, where y represents absorbance and x represents the concentration of the target pollutant.

[0118] The results showed that in the initial reaction stage, only one band was observed in the entire spectrum at 265 nm. As the reaction time increased, the absorption at 265 nm gradually disappeared, and the corresponding absorption peak below 230 nm increased significantly, indicating that most SMX may be degraded into other intermediates or small molecules.

[0119] Figure 3 (b) shows the effect of different pyrolysis temperatures on the ability of catalysts to activate PMS to degrade sulfamethoxazole (SMX). The specific experimental steps are as follows:

[0120] In a typical SMX degradation experiment, in order to determine the catalytic activity of the catalyst for SMX degradation, the composite materials of Example 2, Example 5 and Example 6 (the concentration of the composite materials in the SMX aqueous solution is 0.2 g·L -1 ) dispersed in 50mL, 10mg·L -1, pH = 5.50 SMX aqueous solution in a 100mL conical flask, oscillate in a constant temperature oscillator at 150rpm, 25°C for 1 minute, then add PMS to the solution (the concentration of PMS in the SMX aqueous solution is 0.32mM; and the solution without PMS is used as a control) to start the catalytic degradation reaction. After a certain reaction time (3 minutes, 5 minutes, 10 minutes, 15 minutes and 20 minutes), take out the sample with a 2mL syringe, filter it with a 0.45 micron needle organic filter, and then measure the concentration change of the SMX sample at a wavelength of 265 nanometers by ultraviolet visible spectrophotometry. Its standard curve is y = 0.042x + 0.001, where y represents absorbance and x represents the concentration of the target pollutant.

[0121] The results show that with the increase of pyrolysis temperature, the removal and adsorption capacity of the catalyst for sulfamethoxazole (SMX) are improved; from the curve without adding PMS, it can be seen that the N-doped defective carbon-loaded amorphous Co nanoparticle composite material obtained by the present invention has a slight adsorption effect on SMX.

[0122] Figure 3 (c) shows Co-NCG prepared with different CoNO3·6H2O addition concentrations 15 Remove the change in SMX removal rate. The specific test steps are as follows:

[0123] In a typical SMX degradation experiment, in order to determine the catalytic activity of the catalyst for SMX degradation, the composite materials of Example 2 and Example 8, Comparative Example 2 and Comparative Example 3 (the concentration of the composite materials in the SMX aqueous solution is 0.2 g·L -1 ) dispersed in 50mL, 10mg·L -1 , pH = 5.50 SMX aqueous solution in a 100mL conical flask, oscillate in a constant temperature oscillator at 150rpm, 25°C for 1 minute, then add PMS to the solution (the concentration of PMS in the SMX aqueous solution is 0.32mM) to start the catalytic degradation reaction, after 20 minutes, take out the sample with a 2mL syringe, filter it with a 0.45 micron needle organic filter, and then measure the concentration change of the SMX sample at a wavelength of 265 nanometers by UV-visible spectrophotometry. Its standard curve is y = 0.042x + 0.001, where y represents absorbance and x represents the concentration of the target pollutant.

[0124] The results show that with the increase of Co addition, the ability of the catalyst to activate PMS to remove sulfamethoxazole (SMX) is also affected, and in the range of 0-3 mM, the more Co is added, the stronger the ability of the catalyst to activate PMS to remove sulfamethoxazole (SMX).

[0125] Figure 3(d) shows Co-NCG obtained at different calcination temperatures 15 The removal rate of SMX is affected. The specific test steps are as follows:

[0126] In a typical SMX degradation experiment, in order to determine the catalytic activity of the catalyst for SMX degradation, the composite materials of Examples 1, 2, 3, 7 and Comparative Example 1 (the concentration of the composite materials in the SMX aqueous solution is 0.2 g·L -1 ) dispersed in 50mL, 10mg·L -1 , pH = 5.50 SMX aqueous solution in a 100mL conical flask, oscillate in a constant temperature oscillator at 150rpm and 25°C for 1 minute, then add PMS to the solution (the concentration of PMS in the SMX aqueous solution is 0.32mM; and the solution without PMS is used as a control) to start the catalytic degradation reaction. After 20 minutes, take out the sample with a 2mL syringe, filter it with a 0.45 micron needle organic filter, and then measure the concentration change of the SMX sample at a wavelength of 265 nanometers by ultraviolet visible spectrophotometry. Its standard curve is y = 0.042x + 0.001, where y represents absorbance and x represents the concentration of the target pollutant.

[0127] The results reflect that as the ratio of mixed dicyandiamide increases, the ability of the catalyst to activate PMS to remove pollutants also increases. When the ratio is controlled at 15:1, the degradation rate of sulfamethoxazole (SMX) in the system can reach 97.2% within 20 minutes, and when the ratio of dicyandiamide is continuously increased to 20:1, the removal rate of sulfamethoxazole (SMX) is 97.5%, which does not show a sustained and substantial enhancement. It can be seen from the curve without adding PMS that the obtained N-doped defective carbon-supported amorphous Co nanoparticle composite material of the present invention has a slight adsorption effect on SMX.

[0128] Therefore, considering the above catalyst degradation characteristics and the economic utilization of materials, a Co addition of 3 mM and a dicyandiamide ratio of 15:1 were selected as Co-NCG. 15 catalyst.

[0129] Figure 4 Co-NCG when different concentrations of PMS are added 15 + PMS system MC-LR removal rate (a); different concentrations of Co-NCG 15 Co-NCG 15 + PMS system MC-LR removal rate (b); Effect of initial dissolution pH on Co-NCG 15 +PMS system to remove MC-LR removal efficiency (c); Inorganic ions and humic acid on Co-NCG 15 Effect of +PMS system on the removal rate of MC-LR (d).

[0130] Figure 4 (a) shows the degradation rate of MC-LR under four PMS concentrations (0.00mM, 0.06mM, 0.13mM and 0.19mM). The specific experimental steps are as follows: In a typical operation process, Co-NCG 15 Composite material (the concentration of composite material in SMX aqueous solution is 0.2g·L -1 ) dispersed in 50mL, 2.5mg·L -1 , pH = 6.45 MC-LR aqueous solution in a 100 mL conical flask, oscillate in a constant temperature oscillator at 150 rpm and 25 ° C for 1 minute, and then add PMS to the solution to make the PMS concentration 0.00, 0.06, 0.13 and 0.19 mM, respectively, to start the catalytic degradation reaction.

[0131] In the MC-LR degradation experiment, the catalytic activity of the catalyst in MC-LR degradation was studied in a batch system (HPLC). 1 mL of the solution was taken out at 3 min, 5 min, 10 min, 15 min, 20 min, 25 min and 30 min, and then filtered through a filter membrane and mixed with 0.5 mL of methanol for storage. The MC-LR concentration in the collected samples was determined by HPLC equipped with a UV detector and a C18 reverse phase column. The ratio of methanol to water in the HPLC was 60:40, and the flow rate was 0.60 mL min -1 , λmax=220nmAll experiments were performed in duplicate.

[0132] like Figure 4 As shown in (a), as the PMS concentration increased from 0.06 mM to 0.13 mM, the degradation rate of the system increased from 95.3% to 99.2%. Considering the economic utilization and degradation efficiency of PMS, a PMS dosage of 0.13 mM was used in subsequent experiments.

[0133] Figure 4 Four groups of different catalyst dosages (0.00 g·L -1 , 0.10g·L -1 , 0.12g·L -1 and 0.14 g·L -1 ) to evaluate the effect of catalyst dosage on MC-LR degradation rate. The specific steps are: in a typical operation process, Co-NCG 15 The concentrations of the composite materials in the MC-LR aqueous solution were 0.00, 0.10, 0.12 and 0.14 g·L -1 ) dispersed in 50mL, 2.5mg·L -1, pH = 6.45 MC-LR aqueous solution in a 10 mL conical flask, oscillate in a constant temperature oscillator at 150 rpm and 25°C for 1 minute, then add PMS to the solution to a concentration of 0.13 mM to start the catalytic degradation reaction.

[0134] In the MC-LR degradation experiment, the catalytic activity of the catalyst for MC-LR degradation was studied in a batch system. 1 mL of the solution was taken out at 3 min, 5 min, 10 min, 15 min, 20 min, 25 min and 30 min, respectively, and then filtered through a filter membrane and mixed with 0.5 mL of methanol for storage. The MC-LR concentration in the collected samples was determined by high performance liquid chromatography equipped with a UV detector and a C18 reverse phase column. The ratio of methanol to water in the high performance liquid chromatography was 60:40, and the flow rate was 0.60 mL min -1 , λmax=220nmAll experiments were performed in duplicate.

[0135] from Figure 4 In (b), it can be seen that the catalyst exhibits a certain degree of adsorption to MC-LR, which may be due to the Co-NCG 15 The mesoporous structure of the catalyst was still observed to be limited by the increase in the degradation rate. At the same time, when there was only PMS in the system (without adding Co-NCG 15 Catalyst), only 28.75% of MC-LR could be removed in 30 min. Considering the maximum utilization of catalyst, the subsequent experiments used 0.12 g·L -1 Co-NCG 15 The catalyst participated in the subsequent performance experiment of MC-LR degradation.

[0136] Figure 4 (c) shows the effect of different initial solution pH on the degradation ability of MC-LR. The specific steps are as follows: in a typical operation process, Co-NCG 15 Composite material (the concentration of composite material in MC-LR aqueous solution is 0.12g·L -1 ) dispersed in 50mL, 2.5mg·L -1 A 100 mL conical flask containing an MC-LR aqueous solution (initial pH = 3.00, 5.00, 6.45, 7.00, 8.00 and 9.00) was shaken in a constant temperature oscillator at 150 rpm and 25°C for 1 min, and then PMS was added to the solution to a concentration of 0.13 mM to start the catalytic degradation reaction.

[0137] In the MC-LR degradation experiment, the catalytic activity of the catalyst for MC-LR degradation was studied in a batch system. 1 mL of the solution was taken out at 3 min, 5 min, 10 min, 15 min, 20 min, 25 min and 30 min, respectively, and then filtered through a filter membrane and mixed with 0.5 mL of methanol for storage. The MC-LR concentration in the collected samples was determined by high performance liquid chromatography equipped with a UV detector and a C18 reverse phase column. The ratio of methanol to water in the high performance liquid chromatography was 60:40, and the flow rate was 0.60 mL min -1 , λmax=220nmAll experiments were performed in duplicate.

[0138] The results showed that within the pH range of 3.00 to 8.00, the system still maintained a degradation rate of more than 80.1%, indicating that the system has good pH adaptability and shows the potential for rapid removal of MC-LR.

[0139] Figure 4 (d) shows the effect of adding different inorganic ions on the removal rate of MC-LR. The specific steps are:

[0140] In a typical operation, Co-NCG 15 Composite material (the concentration of composite material in MC-LR aqueous solution is 0.2g·L -1 ) dispersed in 50mL, 2.5mg·L -1 , pH = 6.45 MC-LR aqueous solution (MC-LR aqueous solution contains 25mM Cl - , 25mM HPO4 - , 25mM HCO3 - and 25 mM HA) in a 100 mL conical flask and shaken in a constant temperature oscillator at 150 rpm and 25° C. for 1 minute, then PMS was added to the solution to a concentration of 0.13 mM to start the catalytic degradation reaction.

[0141] In the MC-LR degradation experiment, the catalytic activity of the catalyst for MC-LR degradation was studied in a batch system. 1 mL of the solution was taken out at 3 min, 5 min, 10 min, 15 min, 20 min, 25 min and 30 min, respectively, and then filtered through a filter membrane and mixed with 0.5 mL of methanol for storage. The MC-LR concentration in the collected samples was determined by high performance liquid chromatography equipped with a UV detector and a C18 reverse phase column. The ratio of methanol to water in the high performance liquid chromatography was 60:40, and the flow rate was 0.60 mL min -1 , λmax=220nmAll experiments were performed in duplicate.

[0142] The results showed that after adding 2.5mM Cl- and HCO3 -、H2PO4 - and HA, and in solutions containing 2.5 mg / L of algal toxins, the catalytic system showed good degradation performance, and the system showed good anti-interference ability.

[0143] Figure 5 For Co-NCG 15 Quenching diagram of MC-LR degradation (a); DMPOX image (b), DMPO (DMPO-SO4 ·- , DMPO-·OH)(c) and DMPO(DMPO-O2 ·- )(d);TEMP(TEMP- 1 EPR spectrum of O2 as a scavenger (e) Co-NCG 15 Cycle diagram of multiple degradation of MC-LR.

[0144] Figure 5 (a) shows the effect of adding quencher on MC-LR removal rate. The specific steps are:

[0145] In a typical operation, Co-NCG 15 Composite material (the concentration of composite material in MC-LR aqueous solution is 0.2g·L -1 ) dispersed in 50mL, 2.5mg·L -1 A 50-mL conical flask was placed in a MC-LR aqueous solution (the MC-LR aqueous solution contained 50 mM methanol (MeOH), 50 mM tert-butyl alcohol (TBA), 5 mM p-benzoquinone (BQ), and 5 mM furfuryl alcohol (FFA)) with a pH of 6.45. The solution was oscillated in a constant temperature oscillator at 150 rpm and 25°C for 1 min. Then PMS was added to the solution to a concentration of 0.13 mM to observe the inhibition of the catalytic degradation rate.

[0146] To determine the catalyst repetitive stability, Co-NCG was collected from the solution after the MC-LR catalytic degradation reaction was completed. 15 The catalyst was washed and filtered with ultrapure water and absolute ethanol, and the material obtained after MC-LR degradation was dried under vacuum at 60 °C for the next cycle experiment.

[0147] In the cycling experiment, Co-NCG 15 Composite materials after recycling (the concentration of composite materials in SMX aqueous solution is 0.2 g·L -1 ) dispersed in 50mL, 2.5mg·L -1, MC-LR aqueous solution with initial pH = 6.45 was placed in a 100 mL conical flask and oscillated in a thermostatic oscillator at 150 rpm and 25 ° C for 1 minute, and then PMS was added to the solution to a concentration of 0.13 mM to start the catalytic degradation reaction. In each set of operating parameter experiments, other parameters remained unchanged. All degradation tests were performed three times, and the average values ​​obtained were represented by error bars.

[0148] Figure 5 (a) is the result of free radical quenching, and the electromagnetic paramagnetic resonance results of Figures (b) to (e) show that 1 O2 and SO4 ·- Co-NCG 15 The main contributors to the degradation of MC-LR by the / PMS system are 1 O2 is the main free radical. Figure (f) shows that after four cycles of use, Co-NCG 15 / PMS still maintains a removal rate of more than 80% and has good reusability.

[0149] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An N-doped defective carbon-supported amorphous Co nanoparticle composite material, comprising an N-doped defective carbon skeleton and amorphous Co nanoparticles supported in the N-doped defective carbon skeleton.

2. The N-doped defective carbon-supported amorphous Co nanoparticle composite material according to claim 1, characterized in that: The mass of the amorphous Co nanoparticles is 1-2% of the mass of the N-doped defective carbon-loaded amorphous Co nanoparticle composite material.

3. The N-doped defective carbon-supported amorphous Co nanoparticle composite material according to claim 1, characterized in that: In the N-doped defective carbon skeleton, the doping amount of N atoms is 35-40%.

4. The method for preparing the N-doped defective carbon-supported amorphous Co nanoparticle composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The water-soluble cobalt salt, coffee grounds biochar and water are mixed, and after solid-liquid separation, the obtained solid matter is freeze-dried to obtain biochar loaded with Co ions; The biochar loaded with Co ions and a nitrogen source are mixed and calcined to obtain the N-doped defective carbon loaded amorphous Co nanoparticle composite material; the nitrogen source is dicyandiamide or melamine.

5. The preparation method according to claim 4, characterized in that: The water-soluble cobalt salt includes Co(NO3)2·6H2O; the mass of the water-soluble cobalt salt is 0 to 9.5% of the mass of the coffee grounds biochar, and is not 0.

6. The preparation method according to claim 4 or 5, characterized in that: The freeze-drying temperature is 10-70° C. and the time is 12-24 hours.

7. The preparation method according to claim 4, characterized in that: The mass ratio of the biochar loaded with Co ions to the nitrogen source is 1:(5-20).

8. The preparation method according to claim 4, characterized in that: The calcination temperature is 600-800° C., and the heat preservation time is 2 hours.

9. The preparation method according to claim 4 or 8, characterized in that: The heating rate to the calcination temperature is 3-8°C / min.

10. Use of the N-doped defective carbon-supported amorphous Co nanoparticle composite material as claimed in any one of claims 1 to 3 or the N-doped defective carbon-supported amorphous Co nanoparticle composite material prepared by the preparation method as claimed in any one of claims 4 to 9 as a catalyst in catalyzing the degradation of water pollutants with peroxymonosulfate.

Citation Information

Patent Citations

  • Method for treating antibiotics in water body by coupling magnetic nano material to persulfate

    CN111617731A

  • Coffee residue biochar and method for removing urea in water

    CN113526648A

  • Self-nitrogen-doped porous carbon catalyst loaded with cobalt oxide, preparation method and application thereof

    CN113976158A

  • Preparation of cobalt-based biochar composite material and application of cobalt-based biochar composite material in persulfate oxidation

    CN117563647A

  • Copper-loaded nitrogen-doped biochar composite material as well as preparation method and application thereof

    CN118045571A